Bartonella Henselae: A New Pathogen for Humans - Cornejo Medina, William (1999)
Bartonella henselae has recently been recognized as etiological agent of four clinical syndromes: bacillary angiomatosis, bacillary peliosis hepatis, relapsing fever with bacteremia, and cat-scratch disease. The bacterium has been isolated and fully characterized. Application of newer technologies that isolate, amplify and analyze the B. henselae DNA has helped to solve identification and diagnostic problems, and they are redefining our understanding of a few of the clinical syndromes caused by this microorganism. Over the last years, it has been recognized that population at risk for B. henselae infections has expanded from adults infected with human immunodeficiency virus to transplant patients and, later, immunocompetent adults and children. This article reviews recent information about bacteriological and epidemiological aspects of B. henselae, clinical presentation and treatment of various manifestations of B. henselae infections. In addition, it also summarizes the currently available data on the immune response of human host and methods to diagnose and identify the bacterium. The purpose of this review is to supply information for stimulating the search of B. henselae among peruvian patients.